2022
DOI: 10.1101/2022.10.24.513595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A High Fraction of Oral Bacteria in the Feces Indicates Gut Microbiota Depletion with Implications for Human Health

Abstract: High relative abundance of oral bacteria in the gut is considered abnormal and has been linked to intestinal disorders. However, this reported association has two alternate explanations: ectopic oral bacteria may increase in absolute numbers in the intestine and drive disease (the driver hypothesis) or, instead, intestinal commensals may decrease in absolute numbers and the relative rise in oral bacteria is simply an indicator of this loss (the marker hypothesis). Here we use experiments in mice and clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…4b and 5b ). These findings are consistent with prior work showing that oral microbes are frequently transmitted into the gut 55 and can reach high relative abundances when gut commensals decrease in absolute abundance 56 . We also identified potential opportunistic pathogens 21,48,57 like Klebsiella pneumoniae , Citrobacter freundii , and Streptococcus gallolyticus ( Extended Data Fig.…”
Section: Resultssupporting
confidence: 92%
“…4b and 5b ). These findings are consistent with prior work showing that oral microbes are frequently transmitted into the gut 55 and can reach high relative abundances when gut commensals decrease in absolute abundance 56 . We also identified potential opportunistic pathogens 21,48,57 like Klebsiella pneumoniae , Citrobacter freundii , and Streptococcus gallolyticus ( Extended Data Fig.…”
Section: Resultssupporting
confidence: 92%
“…While inflammatory bowel disease and colon cancer are both conditions where oral taxa are found to be enriched in the gut, recent improvements in quantifying the absolute bacterial load in oral and gut samples has revealed that oral taxa enrichment may be more a reflection of reduced gut bacterial loads. 63 We analyzed the oral-gut microbiota overlap, and found from Venn diagram analysis that 29%, 36%, and 27% of taxa overlapped across the three cohorts (BC, DCIS, healthy), respectively. These results suggest that oral-gut inter-organ translocation was similar across these cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding community dynamics, it remains unclear whether the ectopic colonization by oral bacteria is leading to an expansion of oral bacteria at distant sites or if a decrease in the resident microbiota is leading to a relative increase in these oral bacteria, while the absolute count remains constant (Liao et al 2022 ). Liao et al ( 2022 ) have recently provided evidence that tips the balance in favor of the second option.…”
Section: Pathophysiological and Molecular Mechanisms Associated With ...mentioning
confidence: 99%
“…Regarding community dynamics, it remains unclear whether the ectopic colonization by oral bacteria is leading to an expansion of oral bacteria at distant sites or if a decrease in the resident microbiota is leading to a relative increase in these oral bacteria, while the absolute count remains constant (Liao et al 2022 ). Liao et al ( 2022 ) have recently provided evidence that tips the balance in favor of the second option. Indeed, displacement of autochthonous strains has been observed in several diseases, including IBDs (Metwaly et al 2020 ) or childhood undernutrition (Vonaesch et al 2018 , 2022 ) and it is thus not clear if the disappearance of these strains and/or the overrepresentation of oral strains are the main disease-inducing entities.…”
Section: Pathophysiological and Molecular Mechanisms Associated With ...mentioning
confidence: 99%
See 1 more Smart Citation